2018
DOI: 10.3233/jad-180609
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Reserve with a Translational Approach: Novel Ideas on the Construct and the Interventions

Abstract: The concept of brain, cognitive, and neural reserves has been introduced to account for the apparent discrepancies between neurological damage and clinical manifestations. However, these ideas are yet theoretical suggestions that are not completely assimilated in the clinical routine. The mechanisms of the reserves have been extensively studied in the neurodegenerative pathologies, first of all the Alzheimer's disease. Both human and animal studies addressed this topic by following two parallel pathways. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 117 publications
(181 reference statements)
0
33
0
Order By: Relevance
“…This property can result in clinical tolerance to pathology and reversibility after its removal. The notion of reserve was initially proposed to account for differences in susceptibility of the cerebral cortex to aging or pathological damage [5][6][7][8][9]. In this regard, reserve is defined as a moderator between pathology and outcome [5].…”
Section: Definition Of Cerebellar Reservementioning
confidence: 99%
See 1 more Smart Citation
“…This property can result in clinical tolerance to pathology and reversibility after its removal. The notion of reserve was initially proposed to account for differences in susceptibility of the cerebral cortex to aging or pathological damage [5][6][7][8][9]. In this regard, reserve is defined as a moderator between pathology and outcome [5].…”
Section: Definition Of Cerebellar Reservementioning
confidence: 99%
“…In contrast, cognitive reserve relates to functional activity, such as utilizing "pre-existing cognitive approaches" or "enlisting compensatory approaches" [5]. Since these functional activities depend on the integrity of brain networks, it has been proposed that neural reserve is a consequence of "the efficacy of neural circuitry and the ability to process information" [8], and that these mechanisms contribute to compensation for aging or dementia-related processes [5][6][7][8][9]. In our consideration of cerebellar reserve, we draw attention to this classical meaning of resilience to impairment, and we also highlight the notion of reversibility [10] (Table 1).…”
Section: Definition Of Cerebellar Reservementioning
confidence: 99%
“…In accordance with these observations, the idea has been developed that an enriched brain, that is a brain that modified its neuronal structure as a consequence of complex environmental stimulations, better tolerates the neuronal damage [1][2]. This view assumes the development of cerebral reserves (the brain reserve-BR, the cognitive reserve-CR and finally, the neural reserve-NR) allowing a higher efficiency of the brain networks as well as a more tuned engagement of different neural pathways despite the cerebral damage [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the last thirty years the scientific literature has been increasingly interested in the mechanisms underlying brain and cognitive reserve [1][2]. In fact, several animal and human studies showed the beneficial effects of stimulant life experiences on the structure and functionality of the brain [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation